Dinamika Pengasuhan Bersama Pasca-Perceraian terhadap Kesejahteraan Psikologis Anak: Systematic Literature Review - Faras Salsabila; Afiqah Khairunnisa; Adinda Putri Salisanasti; Joana Deswita; Deliza Syiva Salsabila Nursyam; Rahmadianti Aulia (Jurnal Ilmu Psikologi dan Kesehatan | E-ISSN : 3063-1467, 2026)
This study aims to synthesize previous research findings on the impact of co-parenting quality on children's psychological well-being in divorced families through a systematic literature review approach. The literature search was conducted across five databases (PubMed, SAGE Journals, ScienceDirect, Springer, and Google Scholar), yielding 405 articles (2017–2026), which were then screened based on inclusion and exclusion criteria. The synthesis results show that co-parenting quality, which includes cooperation, effective communication, and low conflict, is positively related to children's psychological well-being, covering mental health, self-esteem, quality of life, autonomy, sense of belonging, and attachment. Co-parenting effectiveness is influenced by parents' emotional conditions, post-divorce conflict levels, and custody arrangements. These findings confirm that children's psychological well-being is the result of the interaction between co-parenting quality and parental psychological conditions. Divorced parents need to maintain healthy cooperation and communication to minimize the negative impact of divorce on their child's growth and development.